2017
DOI: 10.1037/pas0000475
|View full text |Cite
|
Sign up to set email alerts
|

Taking forensic mental health assessment “out of the lab” and into “the real world”: Introduction to the special issue on the field utility of forensic assessment instruments and procedures.

Abstract: The last several decades have seen a major upswing in the development and use of psychological assessment instruments in forensic and correctional settings. At the same time, admissibility standards increasingly have stressed the importance of the reliability and validity of evidence in legal proceedings. Recent research has, however, raised serious concerns about (a) the reliability of forensic science evidence in general, (b) the replicability of psychological research findings in general and in field settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 66 publications
2
79
2
Order By: Relevance
“…Despite this widespread use of the PCL‐R, there are reasons to be concerned about its introduction into clinical and legal decision‐making. Perhaps foremost, a growing body of field literature (see Edens & Boccaccini, ) suggests that scores from this instrument are not particularly reliable in applied contexts in which mental health experts are introducing them. Although the professional manual (Hare, ) provides intraclass correlation (ICC) statistics across various offender samples in the 0.85 and above range, numerous field studies have suggested that it may be closer to 0.60 (or even lower) in adversarial forensic settings (e.g., Edens, Cox, Smith, DeMatteo, & Sörman, ; Miller, Kimonis, Otto, Kline, & Wasserman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this widespread use of the PCL‐R, there are reasons to be concerned about its introduction into clinical and legal decision‐making. Perhaps foremost, a growing body of field literature (see Edens & Boccaccini, ) suggests that scores from this instrument are not particularly reliable in applied contexts in which mental health experts are introducing them. Although the professional manual (Hare, ) provides intraclass correlation (ICC) statistics across various offender samples in the 0.85 and above range, numerous field studies have suggested that it may be closer to 0.60 (or even lower) in adversarial forensic settings (e.g., Edens, Cox, Smith, DeMatteo, & Sörman, ; Miller, Kimonis, Otto, Kline, & Wasserman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychopathic respondents appear willing and able to disclose socially undesirable features of their personality, at least when assured confidentiality in the context of research participation. Furthermore, potential underreporting of psychopathy among offenders only minimally affects the criterion‐related validity of scores from these self‐report measures (Watts et al, ), although, again, findings may not necessarily generalize from research conditions to those settings involving “real‐world” consequences (Edens & Boccaccini, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of field data is a second strength in the methodology of this research; field studies have high ecological validity, meaning that results can be generalized to real-life settings. Two limitations that need to be acknowledged in light of these strengths are (1) implementation fidelity was not formally assessed and (2) the utility of assessment tools is often lower in field studies compared to lab studies (Edens & Boccaccini, 2017).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Field research in the context of Edens and Boccaccini's (2017) review is defined as the collection of assessment data for "the purpose of informing clinical, forensic, or correctional decision-making in regards to the examinee" (p. 600). This could include decisions like release from incarceration or-a primary case management strategy that DRAOR assessments are used for-screening offenders into/out of treatment services (Edens & Boccaccini, 2017). In lab studies, on the other hand, data is collected solely for research purposes and is not used to inform real-world decisions (Edens & Boccaccini, 2017).…”
Section: Strengths and Limitationsmentioning
confidence: 99%